2022
DOI: 10.3390/ma15103451
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multifunctional Spherosilicate-Based Coupling Agents for Improved Bond Strength and Quality in Restorative Dentistry

Abstract: The aim of this study was to investigate the restorative connections of composite materials after fracture, under controlled conditions of treating the materials with novel, spherosilicate-based (SS) primers bearing both methacryl (MA) and trimethoxysilyl (TMOS) groups. The chemistry of methacrylate group insertion and reactive groups hydrolysis has been studied with the aid of 1H NMR (Nuclear Magnetic Resonance) spectroscopy. The light-cured resin composites were repaired by activating the connection site wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These structures are characterized by high activity in catalytic reactions, among which the hydrosilylation of olefins is of the greatest importance, due to the large variety and availability of substrates (also in economic terms), the quantitative nature of the reaction, and the ease of the synthetic procedure. These characteristics determine the growing interest in compounds of the spherosilicate type as functional additives in materials engineering 32 , 35 , 36 or building blocks in polymer chemistry 37 .…”
Section: Introductionmentioning
confidence: 99%
“…These structures are characterized by high activity in catalytic reactions, among which the hydrosilylation of olefins is of the greatest importance, due to the large variety and availability of substrates (also in economic terms), the quantitative nature of the reaction, and the ease of the synthetic procedure. These characteristics determine the growing interest in compounds of the spherosilicate type as functional additives in materials engineering 32 , 35 , 36 or building blocks in polymer chemistry 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The methodology for the synthesis of octaspherosilicate compounds in accordance with the methodology described in our previous work was used in this work. [21]. The reaction temperature was kept below 60°C to mitigate the effects of allyl methacrylate polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Ozer et al reported the solubility of a universal resin composite and a silorane-based resin composite after immersion in a mouth rinse or artificial saliva [15]. In addition to resins and fillers, there are several other components in composite materials such as silane coupling agents, initiators, accelerators, and pigments that might also influence the physical and optical properties [16].…”
Section: Introductionmentioning
confidence: 99%